2017
DOI: 10.2196/resprot.7743
|View full text |Cite
|
Sign up to set email alerts
|

An mHealth Framework to Improve Birth Outcomes in Benue State, Nigeria: A Study Protocol

Abstract: BackgroundThe unprecedented coverage of mobile technology across the globe has led to an increase in the use of mobile health apps and related strategies to make health information available at the point of care. These strategies have the potential to improve birth outcomes, but are limited by the availability of Internet services, especially in resource-limited settings such as Nigeria.ObjectiveOur primary objective is to determine the feasibility of developing an integrated mobile health platform that is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Studies [ 40 , 41 ] have suggested that males have a higher prevalence of HBV compared with females in Nigeria. This may be a consequence of the non-participation of men in their wives or partner’s health program, a paradigm this study initiative is trying to shift among Nigerian men from grassroots [ 22 ]. Regarding parity of women, it was somewhat surprising that nulliparous women had the highest odds of HBV infection in our study contrary to previous studies [ 13 , 15 ] which reported increased odds of HBV infection with increasing parity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [ 40 , 41 ] have suggested that males have a higher prevalence of HBV compared with females in Nigeria. This may be a consequence of the non-participation of men in their wives or partner’s health program, a paradigm this study initiative is trying to shift among Nigerian men from grassroots [ 22 ]. Regarding parity of women, it was somewhat surprising that nulliparous women had the highest odds of HBV infection in our study contrary to previous studies [ 13 , 15 ] which reported increased odds of HBV infection with increasing parity.…”
Section: Discussionmentioning
confidence: 99%
“…The current study leveraged a scale-up of the integrated mhealth intervention to prospectively study a cohort of HIV-infected women of reproductive age receiving care at five comprehensive HIV treatment centers in Benue State, Nigeria. The development of the integrated mHealth platform is described in a previous study [ 22 ]. In brief, the mHealth platform is capable of storing encrypted patient information on a patient-held smartcard and smart phone mobile application.…”
Section: Methodsmentioning
confidence: 99%
“…These approaches allow for enhancing capacity among an expanding pool of retained research-experienced staff. As an example, the two core research coordinators from Baby Shower were absorbed by the University of Nigeria into their Research Resource Center, subsequently working on a different study in another state [ 48 ]. Additionally, five staff from the MoMent and LJM studies were absorbed into NISA’s newly funded Adolescent Coordinated Transition study, currently implemented nationwide [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study design details have been previously described [ 14 ]. We conducted the study in Benue State, north-central Nigeria.…”
Section: Methodsmentioning
confidence: 99%